فعالية الطريقة المباشرة في تعليم مهارة الكلام لطلاب معهد دار السلام كونتور الحرم الحادى عشر اتحاد الأمة فوسو سولاوسى الوسطى: فعالية الطريقة المباشرة في تعليم مهارة الكلام لطلاب معهد دار السلام كونتور الحرم الحادى عشر اتحاد الأمة فوسو سولاوسى الوسطى - Ahsan, Amir; Abdul Qahar Zainal; Wahyuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effectiveness of the direct method in teaching speaking skills to the students of Darussalam Gontor Islamic Boarding Scool Campus Eleventh Ittihadul Ummah Poso Central of Sulawesi. Using a quantitative approach, data were collected through observation, interviews, questionnaires, and documentation analysis. The results showed that the direct method had a significant impact on improving speaking skills, with an effectiveness rate of 76.23%, which is categorized as